The Effect of Lemon Aromatherapy & Murottal Al-Quran on Reducing Pain in Postpartum Mothers: Pengaruh Aromaterapi Lemon & Murottal Al-Quran Terhadap Penurunan Nyeri pada Ibu Postpartum - Indrayani, Eni; Namah, Lutfia Uli; Sofiana, Juni; Dewi, Ivana Chandra (Prosiding University Research Colloquium, 2023)
Background: According to WHO, in 2017 the MMR in the world reached 817 people. In Indonesia, 60% of MMR occurs in the postpartum period and 50% in the 24 hours of the puerperium. Mothers who have given birth complain of pain in the lower abdomen due to contractions which cause pain. The causes of postpartum pain are uterine contractions or involution, breast swelling, tearing of the birth canal and SC surgery. Pain that is felt is physiological occurs during the puerperium. Pain management in postpartum mothers can be done non-pharmacologically by using lemon aromatherapy and murottal Al-Quran Purpose: to implement postpartum midwifery care to reduce pain by providing lemon aromatherapy and murottal Al Quran and its translation. Method: this type of research is descriptive with a pre and post test group case study design. Data obtained from interviews, observation and documentation. The participants were 13 postpartum mothers who met the inclusion criteria. The instruments used are lemon oil, diffusion, writing instruments, recordings of murottal surah Ar-Rahman, observation sheets (NRS) and mobile phones. Results: after 3 weeks of application, 13 participants experienced a decrease in pain from the mild pain category to the no pain category. Conclusion: the application of lemon aromatherapy and murottal Al-Quran can reduce postpartum maternal pain.